A critical reflection on masculine language in Coates’ theory: A case study of female leaders’ speech in Indonesia - Putra, Libra Dui; Winarti, Daru; Handayani, Wiwik Retno; Saputra, Randi; Marni, Silvia; Khandoker, Kamruzzman (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study conducts a critical examination of masculine language features used by female leaders in the public sphere in Indonesia. Based on Coates' (2015) theory of masculinity, this research aims to analyze three main features of masculine language: swearing and taboo language, commands and directives, and questions. The method employed is a qualitative approach based on narrative and content analysis, with secondary data derived from speeches found on relevant YouTube channels. The use of swearing and taboo language serves to assert their dominance in certain situations, while the use of commands and directives demonstrates control and authority. Additionally, rhetorical questions, often associated with masculinity, are used to challenge rigid gender norms. This study shows that masculine language features are not exclusive to men but can also be utilized by women. This research opens new space for discussions about dynamic linguistic identities in social life, particularly in the context of female leadership.